Rebuttal to Koeda et al. (2014) on the Red Sea fishes of the perciform genus Pempheris - Randall, John E.; Victor, Benjamin C.; Alpermann, Tilman J.; Bogorodsky, Sergey V.; Mal, Ahmad O.; Satapoomin, Ukkrit; Bineesh, K. K. (Zootaxa, 2014)
Koeda et al. (2014) published a review of fishes of the genus Pempheris of the Red Sea. They concluded that there are four species: P. adusta Bleeker, P. mangula Cuvier, P. nesogallica Cuvier, and a new species, P. tominagai. We show that the first three species they cite are not present in the Red Sea, as follows. 1) P. adusta is a western Pacific species (type locality Ambon), described only from the holotype, and without a dark border on the anal fin. Koeda et al. (2014) mistakenly apply that name to P. flavicycla which is a widespread Indian Ocean species characterized by a prominent broad black border along the anal fin. Koeda et al. (2014) also redescribe P. adusta, using Indian Ocean specimens of P. flavicycla, despite the coloration difference and a 2.5% difference in the mtDNA sequence (COI) between Indian Ocean and W. Pacific populations. 2) P. mangula is a species from the east coast of India (type locality Visakhapatnam), clearly distinct in both gill-raker counts and a 1.1% sequence divergence in COI from its Red Sea relative P. rhomboidea. Pempheris mangula is not found west of India, and Koeda et al. (2014) mistakenly use DNA from Oman and Madagascar to represent P. mangula, instead of genetic material available from the type locality. 3) Pempheris nesogallica (type locality Mauritius) is unknown from the Red Sea. Koeda et al. (2014) separate P. nesogallica from P. rhomboidea (their “P. mangula”) by eye size; we fail to find any difference (and they use their purported eye-size difference to erroneously rename one of the two syntypes of P. nesogallica as “P. mangula”). 4) Their new species P. tominagai is referred to as the Indian Ocean sister species of “P. schwenkii of the Pacific”; however, the type locality of P. schwenkii is the Batu Islands off the SW coast of Sumatra in the Indian Ocean. They mistakenly include specimens of a distant South African species as paratypes of P. tominagai. We have determined that P. tominagai is a valid species endemic to the Red Sea and Gulf of Aden. They misidentify one lot of P. rhomboidea in the collection of the Hebrew University of Jerusalem as their record of P. nesogallica from the Red Sea. They misidentify the specimen in their photograph of Fig. 1B as P. adusta and use it as material for their redescription of the species, but it is now shown to be a paratype of Pempheris bexillon Mooi & Randall, 2014. Additionally, they regard P. malabarica Cuvier as a junior synonym of P. molucca Cuvier, but the name P. molucca is based on a fanciful painting and is unavailable as a nomen dubium. They treat Pempheris russellii Day as a junior synonym of P. mangula; however, it is distinct in having longer pectoral fins, a larger eye, and more gill rakers. Their key to the species of Pempheris of the Red Sea is incorrect. We present a new key and conclude that only three species of Pempheris are presently known from the Red Sea: P. flavicycla, P. rhomboidea, and P. tominagai.